The impact of smuggling on the customs security of the state - Rohatynska, Nina (Actual problems of law (Aktual’ni problemi pravoznavstva), 2021)
The article considers theoretical issues of determining the content of smuggling. The current problems of smuggling, the prerequisites for its spread in border areas are highlighted. The peculiarities of smuggling and its impact on customs security are substantiated. It is emphasized that one of the main tasks assigned to customs authorities is, among other things, prevention and counteraction to smuggling, combating violations of customs rules throughout the customs territory of Ukraine, as well as exchange of documents and information (including electronic) with other state bodies of Ukraine, customs, law enforcement and other bodies of foreign states. The legal nature of smuggling and its negative impact on customs security has been studied. It is smuggling and violation of customs rules that are the basis for the existence of customs crime. It is an essential component of economic crime, related to embezzlement, evasion of customs duties, and the commission of official crimes. The goal of customs security is defined as achieving the level of efficiency and reliability of the customs system due to the productive functioning of customs authorities. Measures aimed at ensuring customs security in the field of customs policy are analyzed.